Making Genus: Exploring Gender Roles Within Utopian Societies - Nistor, Dariana (Architecture Image Studies, 2021)
The ‘Making Genus’ project comes as a multi-faceted response to an unassuming, mono-directional quest – creating genderless utopia. Spanning across several mediums of expression such as graphics, the moving image and fiction writing, the work encapsulates a textured, non-linear approach to world making processes. Deeply rooted in feminist science fiction and feminist epistemology, the project is defined by an attempt to employ utopian tropes to (re)write speculative narratives. The continuous, deliberate ‘joggling’ exercise between writings, drawings and films unravels a world which gradually opens itself to the reader, viewer, traveller, learner–a world depicting a post-gender utopia, a place where social constructs fade and utopian dreams become tangible realities. The weaving between science fiction, feminist theory and architectural theory comes as the most evident assembly– means of expanding the already “controversial” feminist line of thought to new dimensions, pushing its limits to fictional realms and creating worlds around its premises.